The Role of Audit Risk in Improving Audit Quality - DOLOKSARIBU, Tio Arriela; FIRDAUS, Rizalnur (International Journal of Environmental, Sustainability, and Social Science, 2023)
Audit quality is closely related to the auditor's audit process. Attitude and Cognitive Auditor is very necessary for completing the audit; besides that, audit risk considerations play an important role in decision-making by the auditor. Various ways and processes of audit work also adapt to circumstances that are not usually carried out. Therefore, audit quality needs to be studied more deeply so that in the future, the audit process can remain of high quality in all conditions. This study aims to examine the effect of audit quality in terms of audit skepticism, planning, and risk, which play a moderating role. The sample of this research is 265 auditor respondents in Indonesia. A research method is a quantitative approach tested through path analysis. Statistical testing was carried out using the SmartPLS 3 testing tool. The results showed that professional Skepticism affected audit quality. Furthermore, Audit Planning influences Audit quality. Audit risk is proven to strengthen the relationship between professional Skepticism and audit quality. However, Audit Risk has different results, which does not strengthen the relationship between audit planning and Audit Quality. Therefore, audit risk needs to be corrected and considered by the auditor in terms of professionalism and audit planning. It aims to improve audit quality. Future research can consider the use of information technology, which is a major part of the audit process